Pandemic intake questionnaire to improve quality, effectiveness, and efficiency of outpatient neurologic and developmental care at the Kennedy Krieger institute during the COVID-19 pandemic - Vedmurthy, Pooja; Murray, Connor; Chen, Belinda; Asiedu, Akua; Baranano, Kristin; Bay, Mihee; Belcher, Harolyn; Burton, Vera; Conlon, Charles; Fine, Amena; Gill, Ryan; Harris, Jacqueline; et al. (Frontiers in Rehabilitation Sciences, 2022)
Background The COVID-19 pandemic uniquely affects patients with neurologic and developmental disabilities at the Kennedy Krieger Institute. These patients are at increased risk of co-morbidities, increasing their risk of contracting COVID-19. Disruptions in their home and school routines, and restrictions accessing crucial healthcare services has had a significant impact. Methods A Pandemic Intake questionnaire regarding COVID-19 related medical concerns of guardians of patients was distributed using Qualtrics. Data from May-December 2020 were merged with demographic information of patients from 10 clinics (Center for Autism and Related Disorders (CARD), Neurology, Epigenetics, Neurogenetics, Center for Development and Learning (CDL) Sickle Cell, Spinal Cord, Sturge-Weber syndrome (SWS), Tourette's, and Metabolism). A provider feedback survey was distributed to program directors to assess the effectiveness of this intervention. Results Analysis included responses from 1643 guardians of pediatric patients (mean age 9.5 years, range 0–21.6 years). Guardians of patients in more medically complicated clinics reported perceived increased risk of COVID-19 (p < 0.001) and inability to obtain therapies (p < 0.001) and surgeries (p < 0.001). Guardian responses from CARD had increased reports of worsening behavior (p = 0.01). Providers increased availability of in-person and virtual therapies and visits and made referrals for additional care to address this. In a survey of medical providers, five out of six program directors who received the responses to this survey found this questionnaire helpful in caring for their patients. Conclusion This quality improvement project successfully implemented a pre-visit questionnaire to quickly assess areas of impact of COVID-19 on patients with neurodevelopmental disorders. During the pandemic, results identified several major areas of impact, including patient populations at increased risk for behavioral changes, sleep and/or disruptions of medical care. Most program directors reported improved patient care as a result.